Half Filleted Flap for Thumb Reconstruction A Case Report - Dr. Roy. Knajoor; Dr. C.N. Ramaswamy (Indian Journal of Plastic Surgery)
Major injury to the hand is a difficult problem to treat. Even after best of care, it is often difficult to get the hand rehabilitated back to its full function. In an attempt to preserve all the full complements of the hand, one tends to preserve all the viable tissue even when the functional capability is irrepairably damaged. The end result is a stiff posts which interfere with the basic function of hand. By careful initial assessment of the injury this can be avoided. It is also possible to use viable tissue from damaged finger on to another finger, which is less damaged and whose functional capability is unaffected. Use of a filleted flap is one such method. A case is presented, where full complement of distal phalanx, nail complex and other soft tissues were predicled on the Proximal Filleted skin of Index finger to reconstruct the terminal phalanx of the thumb and the soft tissue of the Thumb web.